Representações sociais de professores sobre a inclusão de alunos autistas nos anos iniciais do ensino fundamental - OLIVEIRA, Luane de Cássia Carvalho de (2021)
This study aims to understand the social representations of teachers in a public school in the city of Bragança-PA about the inclusion of autistic students in the early years of elementary school. With a qualitative approach, four teachers of inclusive regular classes with autistic students participated in the research. The survey took place through semi-structured interviews and socioeconomic questionnaire. Data analysis was performed using Moscovici's Theory of Social Representations (2015) and Bardin's content analysis (2004). The results suggest that teachers' Social Representations (SR) about the inclusion of autistic students are permeated by concerns about interacting the autistic student with the class and involving them in the activities, with a perception of ASD characterized by cognitive, learning and learning issues. relational, highlight the prejudice of parents of non-disabled children and the difficulty of inclusive pedagogical practices, either due to lack of in-service training or lack of conditions in schools (resources, materials, methodologies, support); thus SRs are marked by anxieties, concerns and insecurity about autism. It is concluded that these SR influence directly the achievement of successful inclusive pedagogical practices in school and are directly related to a deficient inclusive educational policy.